Implementation of the Restitution Triangle in Building a Humanistic and Restorative School Culture at Kalibatur State Elementary School - Ari Kusmiyati; Kuntoro Kuntoro (Proceedings Series on Social Sciences & Humanities, 2025)
The increase in negative student behavior and the decline in positive character are challenges in creating a conducive learning environment that supports holistic student development. This can be overcome by implementing the restitution triangle. The purpose of this study was to analyze the effectiveness of the application of the restitution triangle in building a humanistic and restorative school culture at Kalibatur Elementary School. The research method used was qualitative descriptive with a case study approach. Data were collected through observation, interviews, and documentation of students and teachers which were then analyzed thematically to identify the application of the restitution triangle and its impact on school culture. The results showed that this approach helped create a school culture that supports students' social and emotional development, as well as reducing negative behaviors such as bullying and conflict between students. The commitment and support of all school residents, teacher training and skills, student and parent involvement, evaluation and continuous development are factors in the success of this program. This study concludes that the application of the restitution triangle at Kalibatur Elementary School is effective in building a humanistic and restorative school culture. This program is recommended as an innovative model in creating a more positive educational environment and supporting the development of students' character holistically.